The Influence of Online Customer Reviews, Online Customer Ratings and Price on Purchase Intention toward Tokopedia - Adri, Vensa Prita; Mursal, Mursal (Universitas Batam, 2022)
This study aims to determine the effect of Online Customer Review, Online Customer Rating dan Price in Tokopedia on Purchase Intention either partially or simultaneously. This type of research is descriptive with a quantitative approach. The sample selection used purposive sampling, amounting to 125 respondents. The data analysis technique used is classic assumption test, multiple linear regression, dan hypothesis test. Based on the research results obtained: 1) Online Customer Review has positive dan significant relationship in Tokopedia on Purchase Intention used t-test. 2) Online Customer Rating has positive dan significant relationship in Tokopedia on Purchase Intention used t-test. 3) Price has positive but not significant relationship in Tokopedia on Purchase Intention used t-test. 4) Online Customer Review, Online Customer Rating dan Price simultaneously have a positive and significant relationship in Tokopedia on Purchase Intention used F-test